A Study on the Impact of Online Education on Students’ Mental Health: छात्रों के मानसिक स्वास्थ्य पर ऑनलाइन शिक्षा के प्रभाव का अध्ययन - Shukla, Piyush Kumar (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
During the COVID-19 pandemic, the rapid transformation of the education system firmly replaced traditional classroom teaching with online education. While this digital shift created numerous opportunities in the field of education, its adverse effects were also deeply reflected in students’ mental health. On one hand, online education provided students with the freedom to learn from home; on the other, it placed them in a socially, emotionally, and psychologically isolated and pressured environment. Excessive reliance on technological platforms, lack of physical activity, minimal interpersonal interaction, and the compulsion to remain in front of screens for extended periods have had detrimental effects on students’ mental well-being. The greatest drawback of online education has been its tendency to distance students from social contact and the classroom environment. In the traditional education system, interactions with teachers and peers, participation in sports, and engagement in group activities not only contributed to academic growth but also played a vital role in maintaining mental balance and developing social skills among students. Abstract in Hindi Language: कोविड-19 महामारी के दौरान जिस तेजी से शिक्षा प्रणाली में परिवर्तन आया, उसने पारंपरिक कक्षा शिक्षण की जगह ऑनलाइन शिक्षा को मजबूती से स्थापित कर दिया। हालांकि इस डिजिटल बदलाव ने शिक्षा के क्षेत्र में अनेक अवसर उत्पन्न किए, वहीं इसके दुष्परिणाम भी छात्रों के मानसिक स्वास्थ्य पर गहरे रूप से परिलक्षित हुए। ऑनलाइन शिक्षा की सुविधा ने एक ओर जहां छात्रों को घर बैठे शिक्षा प्राप्त करने की स्वतंत्रता दी, वहीं दूसरी ओर इसने छात्रों को सामाजिक, भावनात्मक और मनोवैज्ञानिक दृष्टिकोण से एक प्रकार की एकाकी और दबावपूर्ण स्थिति में डाल दिया। तकनीकी माध्यमों पर अत्यधिक निर्भरता, शारीरिक गतिविधियों की कमी, पारस्परिक संवाद की न्यूनता और निरंतर स्क्रीन पर बने रहने की विवशता ने छात्रों के मानसिक स्वास्थ्य पर प्रतिकूल प्रभाव डाला है। ऑनलाइन शिक्षा की सबसे बड़ी समस्या यह रही है कि यह विद्यार्थियों को सामाजिक संपर्क और कक्षा वातावरण से दूर करती है। पारंपरिक शिक्षा प्रणाली में शिक्षक और सहपाठियों के साथ होने वाला संवाद, खेलकूद, सामूहिक गतिविधियां आदि न केवल शैक्षिक विकास में सहायक होती थीं, बल्कि विद्यार्थियों के मानसिक संतुलन और सामाजिक कौशल के विकास में भी महत्वपूर्ण भूमिका निभाती थीं। Keywords: छात्र, मानसिक स्वास्थ्य, ऑनलाइन शिक्षा के प्रभाव, शिक्षा प्रणाली, कक्षा वातावरण